Solid-phase microextraction probe and application thereof

By introducing perfluoroalkyl groups on porphyrin-based COFs, the Por-COF-F material is synthesized as a coating material for solid phase microextraction probes, the problem of low pretreatment efficiency of PAEs samples in complex substrates is solved, and the problem of low pretreatment efficiency of PAEs samples in complex substrates is achieved. High selective adsorption and enrichment provide new ideas for quantitative detection of PAEs.

CN119425637APending Publication Date: 2025-02-14ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411227171.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems of cumbersome, time-consuming and solvent-consuming pre-treatment of PAEs in complex substrates, and the extraction efficiency of traditional SPME fiber coatings is low, making it difficult to achieve high extraction rate and enrichment efficiency.

Method used

The Por-COF-F material is synthesized as a coating material for solid phase microextraction probe by introducing perfluoroalkyl groups on porphyrin-based COFs through click reaction, and its superhydrophobic surface and abundant hydrogen bond interaction are used. , achieving high selective adsorption and enrichment of PAEs.

Benefits of technology

It realizes efficient enrichment of trace or even ultra-trace PAEs in liquid, provides new ideas for the quantitative detection of (super) trace PAEs in samples, has important promotion significance, and significantly improves the extraction of SPME fibers. efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425637A_ABST
    Figure CN119425637A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-phase microextraction probe and application thereof, a solid-phase microextraction coating of the solid-phase microextraction probe is a Por-COF-F material, and the material is prepared from 1H, 1H, 2H, 2H-perfluorodecanethiol and a porphyrin covalent organic framework through a click reaction. According to the solid-phase microextraction coating disclosed by the invention, a perfluoroalkyl group is introduced into a porphyrin covalent organic framework, so that the coating has a super-hydrophobic surface, and PAEs can be selectively adsorbed through a hydrophobic effect; n, O and F atoms in the coating material can form abundant hydrogen bonds with PAEs for interaction; the aromatic ring structure of the perfluoroalkyl group is changed, and the perfluoroalkyl group and a benzene ring in PAEs can form pi-pi stacking interaction. Due to the interaction, the method shows relatively high selectivity on PAEs, and enrichment of (ultra) trace PAEs in a complex matrix can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid phase microextraction, and in particular to a solid phase microextraction probe and application thereof. Background Art

[0002] Phthalates (PAEs) are a class of colorless organic compounds that can improve the flexibility of plastic products. They are widely used in building materials, medical devices, furniture, toys and other fields. Among them, low molecular weight PAEs such as dimethyl phthalate (DMP), dibutyl phthalate (DBP), and diethyl phthalate (DEP) are used as ingredients in drugs, inks, pesticides, and personal care products to improve product quality. PAEs are combined with plastics in the form of non-chemical bonds, so they are easily released into the environment through migration and evaporation. Studies have shown that PAEs can enter the human body through breathing or skin, accumulate in the human body, interfere with the normal function of the human endocrine system, and are classified as reproductive toxicants. Therefore, establishing an accurate and sensitive method to determine PAEs in actual samples is of great significance for environmental monitoring and research.

[0003] At present, the pretreatment of PAEs samples in complex matrices mainly includes liquid-liquid extraction (LLE), magnetic solid phase extraction (MSPE) and solid phase extraction (SPE), but these traditional pretreatment methods usually have the limitations of cumbersome steps, time-consuming and solvent-consuming. Therefore, rapid, sensitive, portable and environmentally friendly sample pretreatment technologies are more popular among scientific researchers. Solid phase microextraction (SPME) overcomes the defects of traditional sample pretreatment technology, integrates sampling, extraction, concentration and injection, greatly speeds up the speed of analysis and detection. Its significant technical advantages are attracting widespread attention from analysts in the environment, food and pharmaceutical industries, and are vigorously promoted and applied. However, for SPME, its extraction efficiency depends largely on the fiber coating. Therefore, the development of fiber coating materials with high extraction rate and enrichment efficiency is of great significance for the analysis of PAEs samples in complex matrices.

[0004] Porphyrin-based covalent organic frameworks (COFs) have significant advantages due to their large specific surface area, adjustable pore structure, and simple functionalization, but traditional porphyrin-based COFs have limited surface functional groups and general stability. Therefore, how to further enrich the active sites in the porphyrin-based COFs skeleton to obtain new porphyrin-based COFs SPME coating materials with high stability, high adsorption capacity, fast adsorption / desorption rate, and good selectivity is crucial to achieve the analysis of (ultra) trace PAEs in complex and multi-interference environmental media. Summary of the invention

[0005] In view of this, the first object of the present invention is to provide a solid phase microextraction probe, and the second object of the present invention is to provide an application of the solid phase microextraction probe.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The solid phase microextraction probe of the present invention comprises a carrier and a solid phase microextraction coating coated on the surface of the carrier, wherein the solid phase microextraction coating is a Por-COF-F material, and the Por-COF-F material is synthesized from 1H, 1H, 2H, 2H-perfluorodecanethiol and a porphyrin covalent organic framework through a click reaction; The porphyrin covalent organic framework is synthesized from tetraaldehyde phenylporphyrin, 2,5-diethoxyterephthaloylhydrazide and 2,5-bis(allyloxy)terephthaloylhydrazide through a Schiff base reaction; The coating length of the solid phase microextraction coating is 1 to 2 cm, and the coating thickness is 30 μm to 60 μm.

[0007] The beneficial effects are as follows: the present invention introduces perfluoroalkyl groups on porphyrin-based COFs through a click reaction, changes the surface structure and hydrophilicity of COF, and makes it have a super-hydrophobic surface, which is conducive to the adsorption of hydrophobic PAEs through hydrophobic-hydrophobic interactions; the coating material of the present invention has a large number of N, O, and F atoms, which can form rich hydrogen bond interactions with PAEs, and the perfluoroalkyl groups in the coating material change its aromatic ring structure, so that it can form π-π stacking interactions with the benzene rings in PAEs, thereby showing higher selectivity for PAEs, and can achieve the enrichment of trace or even ultra-trace PAEs in liquids, providing a new idea for the quantitative detection of (ultra) trace PAEs in samples, which has important promotion significance.

[0008] Preferably, the solvent for the Schiff base reaction is 1,2-dichlorobenzene and n-butanol in a volume ratio of 1:1, the catalyst is 8 M to 12 M acetic acid aqueous solution, the reaction temperature is 120° C. to 140° C., and the reaction time is 48 h to 72 h.

[0009] Preferably, the specific content of the click reaction is: first ultrasonically disperse the porphyrin covalent organic framework in trifluorotoluene, add AIBN and 1H,1H,2H,2H-perfluorodecanethiol, react at 60°C for 8 h to 24 h under nitrogen protection, wash with acetone after the reaction, and obtain the Por-COF-F material after drying.

[0010] Preferably, the solid phase microextraction coating is adhered to the carrier by glue, specifically comprising: first cleaning and removing impurities from the carrier; then immersing the carrier in the glue to obtain a thin and uniform glue layer; using the glue to adhere the Por-COF-F material, and drying at high temperature; repeating this 2 to 3 times, and finally performing high temperature aging to obtain the solid phase microextraction probe. The carrier can be a stainless steel wire, a stainless steel fiber, or a stainless steel acupuncture needle.

[0011] More preferably, the high-temperature drying temperature is 140° C. to 160° C., and the drying time is 20 min to 40 min; the high-temperature aging temperature is 260° C. to 280° C., and the aging time is 30 min to 60 min.

[0012] More preferably, the glue is a cyclohexane solution of polydimethylsiloxane.

[0013] The present invention also provides the application of solid phase microextraction probe in quantitative detection of trace or ultra-trace phthalates. That is, phthalates are enriched and extracted using solid phase microextraction probe, and the specific enrichment and extraction conditions are: the extraction time is 40 min to 60 min, and the stirring rate during the extraction process is 500 to 700 rpm; after the extraction, the SPME fiber is desorbed and quantitatively analyzed.

[0014] More preferably, the desorption conditions are: desorption temperature is 280°C, desorption time is ≤ 6 min; after desorption, the SPME fiber is quantitatively analyzed by GC-MS / MS. The initial oven temperature of GC-MS / MS is 100°C, maintained for 1 min; then 30°C min -1 Raise the temperature to 200℃ and then at 3℃ min -1 The temperature was raised to 260°C and then at 30°C min -1 Raise the temperature to 300°C and maintain for 9 minutes.

[0015] The beneficial effect is that the fluorine chain modified porphyrin covalent organic framework material of the present invention, as an SPME coating material, shows high selectivity for PAEs. The present invention constructs a quantitative detection method for PAEs based on the probe, which can achieve quantitative detection of up to thirteen PAEs, has ultra-low detection limit and quantitative limit, high sensitivity and high accuracy, and reproducibility, and can achieve accurate detection of trace or even ultra-trace PAEs, providing a new detection idea for PAEs and their metabolites in complex matrices. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the synthesis route of Por-COF-F of the present invention.

[0017] Figure 2 This is a SEM characterization diagram of the present invention. In the diagram, a is Por-COF, b is Por-COF-F, and c is an SPME fiber with a Por-COF-F coating.

[0018] Figure 3 TEM and EDS images of Por-COF of the present invention.

[0019] Figure 4TEM and EDS images of Por-COF-F of the present invention.

[0020] Figure 5 It is the infrared characterization spectrum of Por-COF and Por-COF-F of the present invention.

[0021] Figure 6 It is a thermal stability characterization spectrum of Por-COF and Por-COF-F of the present invention.

[0022] Figure 7 is the water contact angle of Por-COF and Por-COF-F of the present invention.

[0023] Figure 8 It is a comparison chart of the enrichment of the Por-COF-F fiber of the present invention and commercial fibers PDMS and PDMS / DVB. DETAILED DESCRIPTION

[0024] The present invention is described in more detail below with reference to the specific drawings. It should be noted that the PAEs of the present invention include but are not limited to DMP, DIBP, DEEP, DHXP, DBEP, DNOP, DNP, DEP, DBP, DNPP, BBP, DCHP and DEHP, and the corresponding structural formulas are shown in Table 1.

[0025] Table 1 Structural formula of PAEs Example 1 Preparation of solid phase microextraction coating for solid phase microextraction probe The solid phase microextraction coating of the present invention adopts Por-COF-F material. The synthesis route of the Por-COF-F material is shown in Figure 1 , specifically including the following: In the first step, tetraaldehyde phenylporphyrin (16 mg), 2,5-diethoxyterephthaloylhydrazide (6.21 mg), and 2,5-bis(allyloxy)terephthaloylhydrazide (6.74 mg) were added to a Pyrex tube, and then 1,2-dichlorobenzene (0.5 mL) and n-butanol (0.5 mL) were added as solvents, and 12 M acetic acid aqueous solution (0.5 mL) was used as a catalyst. After ultrasonic homogenization, it was degassed through three freeze-pump-thaw cycles, and the Pyrex tube was sealed with a flame and reacted at 120°C for 72 h. After the reaction was completed, the precipitate was collected by centrifugation (or filtration), and placed in a vacuum drying oven at 80°C for vacuum drying for 10 h to obtain a porphyrin covalent organic framework (i.e., Por-COF), whose structural formula is: ; In the second step, Por-COF was ground into powder, 10 mL of trifluorotoluene was added to 100 mg of Por-COF powder, and ultrasonication was performed to uniformly disperse Por-COF in trifluorotoluene. Subsequently, a catalytic amount of azobisisobutyronitrile (AlBN) and 1H,1H,2H,2H-perfluorodecanethiol (2 mL) were added, and the mixture was reacted in an oil bath or water bath at 60°C for 12 h under nitrogen protection. The precipitate was collected by centrifugation, washed with acetone, and vacuum dried at 50°C for 10 h to obtain a fluorine chain-modified porphyrin covalent organic framework material, Por-COF-F, whose structural formula is: Example 2 Preparation of the solid phase microextraction probe of the present invention The present invention uses the Por-COF-F material prepared in Example 1 as a coating material for a solid phase microextraction material to prepare a solid phase microextraction probe, specifically as follows: The first step is to cut a piece of stainless steel wire (of course, stainless steel fiber or stainless steel acupuncture needle can also be used) and use ultrapure water, methanol and acetone to ultrasonically clean it to remove impurities, dry it naturally, and set it aside; In the second step, 2 mL of cyclohexane was added to 1 g of polydimethylsiloxane (PDMS) glue, and the PDMS and cyclohexane were thoroughly mixed by ultrasound until no bubbles appeared in the mixed solution to obtain PDMS glue solution; The third step is to immerse the dried stainless steel wire into the PDMS glue solution, then slowly withdraw it and gently roll it on the filter paper to obtain a thin and uniform glue layer. The stainless steel wire was pressed into the Por-COF-F powder and rotated in the same direction to obtain a uniform coating. The coated fiber was dried at 150 °C for 30 min to solidify the colloid and remove the cyclohexane. In the fourth step, repeat the third step 2-3 times to make the Por-COF-F coating on the stainless steel wire 1.0 cm in length and 40 μm in thickness; install the prepared probe in the SPME sleeve and age it at 270 °C for 40 min (aging can be performed using the gas chromatography injection port) to obtain a solid phase microextraction probe.

[0026] Example 3 Characterization of Por-COF, Por-COF-F and Solid Phase Microextraction Probe 1. The morphology of Por-COF, Por-COF-F materials and Por-COF-F fibers was observed by SEM. Por-COF showed a morphology of stacked particles, and Por-COF-F after fluorine chain modification also showed a stacked state. See Figure 2 (a) and Figure 2 (b) By Figure 2(c) It can be seen that the Por-COF-F fiber coating prepared by physical coating method has a uniform and compact surface, and the thickness of the fiber coating is about 40 μm.

[0027] 2. The morphology of the Por-COF and Por-COF-F material particle stacking was further verified by TEM. Figure 3 and Figure 4 .Depend on Figure 3 (a) and 4 (a), the particle shapes of Por-COF-F and Por-COF stacking are consistent; from the elemental spectrum of Por-COF ( Figure 3 (b)-(d)) show that C, N, and O elements are evenly distributed throughout the material; from the elemental spectrum of Por-COF-F ( Figure 4 (b)-(f)) It can be observed that C, N, O, F, and S are uniformly distributed throughout the material, confirming the successful synthesis of Por-COF-F material.

[0028] 3. Characterize Por-COF and Por-COF-F by FT-IR. Figure 5 It can be seen that Por-COF is at 1664 cm -1 The stretching vibration peak of C=N appeared at 1699 cm -1 C=O and 3330 cm -1 The characteristic peaks of NH stretching vibration nearby disappeared, indicating the successful synthesis of Por-COF. -1 The stretching vibration peak of the CF bond appeared at , indicating the occurrence of a click reaction. The perfluoroalkyl group was successfully bound to Por-COF, which once again confirmed the successful synthesis of Por-COF-F.

[0029] 4. From the thermogravimetric curves of Por-COF and Por-COF-F ( Figure 6 ) It can be seen that before 350 °C, Por-COF and Por-COF-F produced 6.5% and 4% weight losses, respectively. These losses were mainly due to the volatilization of organic solvents and water. The results showed that they have excellent thermal stability and can withstand the high temperature of the GC inlet, so they are suitable for preparing SPME coatings.

[0030] 5. The water contact angles of Por-COF and Por-COF-F were measured. The water contact angles of Por-COF and Por-COF-F were 113° and 129°, respectively (see Figure 7), the hydrophobicity of Por-COF-F is improved compared with that of Por-COF, which indicates that the introduction of perfluoroalkyl groups changes the chemical structure of Por-COF and generates a better hydrophobic surface. On the one hand, a better hydrophobic surface can better isolate the water environment and enhance the stability of the fiber during immersion SPME, thereby improving the durability of the fiber; on the other hand, the enhanced hydrophobicity makes Por-COF-F easier to adsorb hydrophobic phthalates, thereby achieving a better enrichment effect.

[0031] Example 4 Application of the solid phase microextraction probe of the present invention in quantitative detection of PAEs The present invention is based on the probe prepared in Example 2 and combines GC-MS / MS to construct a quantitative detection method for PAEs. The method is to enrich and extract PAEs with the probe, and desorb and quantitatively analyze the extracted probe with GC-MS / MS, which specifically includes the following contents: Place the sample solution or standard solution in a glass bottle, seal it with a PTFE silicone diaphragm and fix it on a water bath; completely immerse the coating part on the probe in the sample solution or standard solution, and stir it at 50°C to allow the probe to better enrich the target analytes in the sample solution or standard solution; the stirring speed is 700rpm, and the stirring enrichment time is 40min; after the enrichment and extraction is completed, retract the probe into the injection needle, and immediately pull it out and send it to the 280°C gas chromatography injection port for desorption, and the desorption time is 6min; After desorption, qualitative and quantitative analysis was performed using a Shimadzu QP-8050 NX gas chromatograph-mass spectrometer (Japan). Chromatographic separation was performed using a HP-5MS (Shimadzu, Japan) capillary column (30 m × 0.25 mm id × 0.25 μm). The initial oven temperature was set at 100 °C for 1 min and then at 30 °C min -1 Raise the temperature to 200℃ and then at 3℃ min -1 The temperature was raised to 260°C and then at 30°C min -1 Raise the temperature to 300°C and maintain for 9 min.

[0032] Example 4 Reliability of the detection method constructed in Example 3 of the present invention 1. Prepare a mixed standard stock solution of 13 PAEs (of course, the stock solution of each phthalate ester can also be prepared separately), the stock solution concentration is 1000 mg / L; dilute the stock solution in a gradient manner to obtain standard solutions with different gradient concentrations; perform quantitative analysis on the standard solution according to Example 3 to establish a standard curve. The results are shown in Table 2.

[0033] Table 2 Standard curves, limits of quantification and limits of detection of 13 PAEs As shown in Table 2, the 13 PAEs showed good linear relationships in the range of 1-500 ng / L. 2 All of them were greater than 0.990, the detection limit was 0.000041-3.81 ng / L, and the quantification limit was 0.00014-12.70 ng / L, achieving accurate quantitative detection of (ultra) trace PAEs with high sensitivity.

[0034] 2. The accuracy of a single probe and between different probes was investigated using a standard solution with a concentration of 200 ng / L, and the results are shown in Table 2. As shown in Table 2, the intra-day and inter-day relative standard deviations (RSDs, n=3) of a single probe were 0.1% to 9.8% and 0.4% to 8.8%, respectively, and the relative standard deviation between different probes was 2.2% to 9.7%, further proving that the detection method constructed by the present invention has good repeatability and reproducibility.

[0035] 3. As shown in Table 2, the enrichment factor of PAEs is 194-5255. The results show that the Por-COF-F of the present invention has good selectivity and enrichment ability for PAEs.

[0036] 4. The present invention uses 30 μm PDMS and 65 μm PDMS / DVB commercial fibers as comparison, and the enrichment, extraction and detection are the same as in Example 3. The results are shown in Figure 8 .Depend on Figure 8 It can be seen that the enrichment and extraction effect of the Por-COF-F fiber of the present invention on the target analyte PAEs is significantly better than that of the two commercial fibers, and its enrichment and extraction rates are 4.4 to 44.7 times and 2.1 to 5.5 times that of the PDMS fiber and PDMS / DVB fiber, respectively.

[0037] 5. In order to verify the accuracy and applicability of the established method in actual matrices, the present invention added PAEs standard solutions of low, medium and high concentration levels (10 ng / L, 50 ng / L, 200 ng / L) to snow water samples, and used the method constructed in Example 3 for enrichment, extraction and detection. The results are shown in Table 3.

[0038] Table 3 Recovery of PAEs spiked into actual snow water samples by Por-COF-F fiber As shown in Table 3, in the snow water matrix, the chromatograms of the target PAEs all showed corresponding peaks, and the spiked recovery of the snow water samples was 73.3-120.7%, and the RSD of the actual samples was 0.9-11.9%. The results prove the accuracy and applicability of the detection method constructed by the present invention for quantifying PAEs in water matrix.

[0039] Example 5 Application of Por-COF-F of the present invention in quantitative detection of PAEs in actual samples The present invention collects snow samples from five universities, five living areas and four industrial areas in a certain place (collected directly when snowing), the snow samples are placed in glass flasks (baked at 550°C before use), and sealed and packaged after the snow melts naturally; the snow samples are centrifuged and filtered with a 0.22 μm filter membrane to remove insoluble particles, and if they cannot be processed in time, they are stored in a refrigerator at 4°C; the detection method of Example 3 is used for quantitative detection, and the results are shown in Tables 4 to 6.

[0040] Table 4 Detection results of PAEs in snow samples from five universities in a certain area Table 5 Detection results of PAEs in snow samples from five residential areas in a certain place Table 6 Detection results of PAEs in snow samples from four industrial areas in a certain place The results show that the higher content of DMP, DIBP, DBP, and DEHP in the snow samples of colleges and universities is 265.7 ng / L, 332.2 ng / L, 321.7 ng / L, and 191.7 ng / L, respectively; the higher content of DBP, DEEP, DEHP, and DNOP in the living area is 210.2 ng / L, 300.4 ng / L, 440.9 ng / L, and 223.5 ng / L, respectively; the higher content of DIBP, DBP, DEEP, and DEHP in the industrial area is 339.8 ng / L, 261.2 ng / L, 206.7 ng / L, and 221.3 ng / L, respectively. It can be seen that the PAEs in the atmosphere of this area mainly include DMP, DIBP, DBP, DEHP, DEEP, and DNOP.

[0041] In summary, the probe of the present invention uses the superhydrophobic material Por-COF-F modified with a perfluoroalkyl group as a coating. The material has a superhydrophobic surface, which is conducive to the adsorption of hydrophobic PAEs through hydrophobic-hydrophobic interactions. The material contains a large number of N, O, and F atoms, which can form rich hydrogen bond interactions with PAEs. The perfluoroalkyl groups in the material change its aromatic ring structure, enabling it to form π-π stacking interactions with the benzene rings in PAEs, and exhibits higher selectivity for PAEs.

[0042] The present invention develops a quantitative detection method for phthalates based on a probe with a Por-COF-F coating in combination with GC-MS / MS. The method has an ultra-low detection limit, good accuracy, and high sensitivity. It can be used for the quantitative detection of (ultra) trace PAEs in complex matrices and has important promotion value.

Claims

1. A solid phase microextraction probe, comprising a carrier and a solid phase microextraction coating coated on the surface of the carrier, characterized in that: The solid phase microextraction coating is a Por-COF-F material, and the Por-COF-F material is synthesized from 1H, 1H, 2H, 2H-perfluorodecanethiol and a porphyrin covalent organic framework through a click reaction; The porphyrin covalent organic framework is synthesized from tetraaldehyde phenylporphyrin, 2,5-diethoxyterephthaloylhydrazide and 2,5-bis(allyloxy)terephthaloylhydrazide through a Schiff base reaction; The coating length of the solid phase microextraction coating is 1 to 2 cm, and the coating thickness is 30 μm to 60 μm.

2. The solid phase microextraction probe according to claim 1, characterized in that: The solvent of the Schiff base reaction is 1,2-dichlorobenzene and n-butanol in a volume ratio of 1:1, the catalyst is 8 M to 12 M acetic acid aqueous solution, the reaction temperature is 120° C. to 140° C., and the reaction time is 48 h to 72 h.

3. The solid phase microextraction probe according to claim 1, characterized in that: The click reaction comprises the following steps: firstly, ultrasonically dispersing the porphyrin covalent organic framework in trifluorotoluene, adding AIBN and 1H,1H,2H,2H-perfluorodecanethiol, reacting at 60° C. for 8 h to 24 h under nitrogen protection, washing with acetone after the reaction, and obtaining the Por-COF-F material after drying.

4. The solid phase microextraction probe according to claim 1, characterized in that: The solid phase microextraction coating is adhered to the carrier by means of glue, which specifically includes the following steps: firstly, the carrier is cleaned and impurities are removed; then, the carrier is immersed in the glue to obtain a thin and uniform glue layer; the Por-COF-F material is adhered by the glue and dried at high temperature; this is repeated 2 to 3 times, and finally, high temperature aging is performed to obtain the solid phase microextraction probe.

5. The solid phase microextraction probe according to claim 4, characterized in that: The high temperature drying temperature is 140° C. to 160° C., and the drying time is 20 min to 40 min; the high temperature aging temperature is 260° C. to 280° C., and the aging time is 30 min to 60 min.

6. The solid phase microextraction probe according to claim 4, characterized in that: The glue is a cyclohexane solution of polydimethylsiloxane.

7. Use of the solid phase microextraction probe according to any one of claims 1 to 6 in the quantitative detection of trace or ultra-trace phthalates, wherein: The application is to enrich and extract phthalates using a solid phase microextraction probe.

8. The use according to claim 7, characterized in that: The enrichment and extraction conditions of phthalates were as follows: the extraction time was 40 min to 60 min, and the stirring rate during the extraction process was 500 to 700 rpm; After extraction, the SPME fiber was desorbed and quantitatively analyzed.

9. The use according to claim 8, characterized in that: After enrichment and extraction, the SPME fiber was subjected to high temperature desorption and quantitative analysis by GC-MS / MS, with a desorption temperature of 280 °C and a desorption time of ≤6 min; The initial oven temperature of GC-MS / MS was 100 °C and maintained for 1 min; then it was heated to 30 °C min -1 Raise the temperature to 200℃ and then at 3℃ min -1 The temperature was raised to 260°C and then at 30°C min -1 Raise the temperature to 300°C and maintain for 9 min.